Teaching students on the specialty “Technology of Perfume-Cosmetic Preparations” in Zaporizhzhya State Medical University the legal aspects of pharmacist-cosmetologists professional activities - Alekseeva, I. M.; Tkachenko, N. O.; Chervonenko, N. M.; Demchenko, V. O.; Zarichna, T. P. (Zaporozhye Medical Journal, 2013)
The article refl ects the experience of teaching the legal aspects of professional activities of pharmacists-cosmetologists to the students of Pharmaceutical Faculty, specialty «Technology of perfumery and cosmetics» in Zaporozhye State Medical University.